Investigation of the Effect of Six Weeks of Integrated Plyometric Exercise Intervention on Vertical Jump Performance of 16- 18 Age Group Male Football Players - Bayram, Mehmet (My University, 2025)
ABSTRACT Title of Thesis: Investigation of the Effect of Six Weeks of Integrated Plyometric Exercise Intervention on Vertical Jump Performance of 16- 18 Age Group Male Football Players Student Name, Surname: Mehmet BAYRAM Supervisor Title, Name, Surname: Prof. Dr. Salih PINAR Program: Exercise and Sports Sciences This study aimed to investigate the effect of a six-week integrated plyometric training model applied to football players on vertical jump performance. 60 male football players, 20% of whom were 16, 80% of whom were 17 and 18 years old, participated in the study. 30 athletes were divided into experimental group and 30 athletes were divided into control group. Integrated training method including plyometric exercises was applied to the 30-person experimental group during the six-week training period. No intervention was applied to the control group. Integrated plyometric training was applied to the experimental group 2 days a week for six weeks. Trainings were applied as general warm-up, dynamic warm-up and integrated plyometric training. Exercises consisted of 3 sets. 1 minute rest was given between sets. First and last test results showed that the vertical jump performance of the study group increased by 6,97 cm. The vertical jump performance of the control group decreased by 0,27 cm. As a result, it was seen that the six-week integrated plyometric training model applied to the experimental group increased vertical jump performance. The control group, to which the training model was not applied, showed a decrease in vertical jump performance when the pre-test and post-test difference was examined. In the light of these results, it can be said that this integrated plyometric training model will be an example for sports scientists and athletes working in this field.

ÖZET Tezin Başlığı: Altı Haftalık Bütünleşik Pliometrik Egzersiz Müdahalesinin 16-18 Yaş Grubu Erkek Futbolcuların Dikey Sıçrama Performansına Etkisinin İncelenmesi Öğrencinin Adı Soyadı: Mehmet BAYRAM Danışmanın Unvanı Adı Soyadı: Prof. Dr. Salih PINAR Program: Egzersiz ve Spor Bilimleri Bu çalışmada, futbolculara uygulanan altı haftalık bütünleşik pliometrik antrenman modelinin dikey sıçrama performanslarına etkisinin incelenmesi amaçlanmıştır. Çalışmaya, yaş ortalamaları %20'si 16, %80'i 17 ve 18 yıl olan 60 erkek futbolcu katılmıştır. 30 sporcu deney grubu, 30 sporcu kontrol grubu olarak ayrılmıştır. Altı haftalık antrenman sürecinde, 30 kişilik deney grubuna pliometrik egzersizleri barındıran bütünleşik antrenman metodu uygulanmıştır. Kontrol grubuna hiçbir müdahale uygulanmamıştır. Deney grubuna altı hafta boyunca, haftada 2 gün bütünleşik pliometrik antrenman uygulanmıştır. Antrenmanlar; genel ısınma, dinamik ısınma ve bütünleşik pliometrik antrenman şeklinde gerçekleştirilmiştir. Egzersizler, 3 setten oluşmaktadır. Setler arası 1 dakika dinlenme yapılmıştır. İlk ve son test sonuçlarına göre, çalışma grubunun dikey sıçrama performansı 6,97 cm artmıştır. Kontrol grubunun dikey sıçrama performansı ise 0,27 cm azalma göstermiştir. Sonuç olarak, deney grubuna uygulanan altı haftalık bütünleşik pliometrik antrenman modelinin, dikey sıçrama performansını artırdığı görülmüştür. Antrenman modelinin uygulanmadığı kontrol grubunun ise dikey sıçrama performanslarında, ön test ve son test farkına bakıldığında, azalma göstermiştir. Bu sonuçlar ışığında, uygulanan bu bütünleşik pliometrik antrenman modelinin, bu alanda çalışma yapan spor bilimcilere ve sporculara örnek olacağı söylenebilir.
Altı Haftalık Bütünleşik Pliometrik Egzersiz Müdahalesinin 16-18 Yaş Grubu Erkek Futbolcuların Dikey Sıçrama Performansına Etkisinin İncelenmesi
Keywords: Sports; Spor